2020
DOI: 10.1002/solr.202000254
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Temperature Crystallization of CsPbIBr2 Perovskite for High Performance Solar Cells

Abstract: Organic-inorganic metal halide perovskites are superstars for photovoltaics and optoelectronics due to their excellent defect tolerance, high charge mobility, tunable optical bandgap, and high absorption coefficient. [1-3] In fact, their power conversion efficiency (PCE) has been increased from 3.8% to 25.2% in just a few years. [4-6] Unfortunately, the organic components in the perovskite composition make them susceptible to stressing conditions including high temperature, chemical, and ultraviolet radiation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 42 publications
(49 reference statements)
0
21
0
Order By: Relevance
“…In general, V OC varies logarithmically with light intensity ( I ), obeying Equation ()VOC=nκTelnIwhere n is the ideality factor, κ is the Boltzmann constant (1.38 × 10 −23 J K −1 ), e is unit electronic charge, and T is absolute temperature (290 K). [ 56 ] The fitted n values for the devices without and with FMAC are 1.82 and 1.43, respectively. It has been recognized that the deviation of this slope from κT/e is triggered by trap‐assisted recombination.…”
Section: Resultsmentioning
confidence: 99%
“…In general, V OC varies logarithmically with light intensity ( I ), obeying Equation ()VOC=nκTelnIwhere n is the ideality factor, κ is the Boltzmann constant (1.38 × 10 −23 J K −1 ), e is unit electronic charge, and T is absolute temperature (290 K). [ 56 ] The fitted n values for the devices without and with FMAC are 1.82 and 1.43, respectively. It has been recognized that the deviation of this slope from κT/e is triggered by trap‐assisted recombination.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al 91 used n-butylammonium iodide (BAI) in CsPbBr 2 I to improve factors like the crystallization and morphology of the structure. The BAI incorporation decreases the trap state density and nonradiative recombination and thereby facilitates preparation at the reduced annealing temperature.…”
Section: Stability Of Cspbxmentioning
confidence: 99%
“…27 Zhang et al proposed low-temperature crystallization of CsPbIBr 2 film through n-butylammonium iodide (BAI) organic additive, overcoming the voltage loss. 28 It is revealed that additives, passivation layers and interfacial layers are essential to improve the perovskite film quality, device performance and stability.…”
Section: Introductionmentioning
confidence: 99%